IMPLEMENTATION OF MULTICULTURAL EDUCATION-BASED PAI LEARNING POLICY AT SMKN 4 CILEGON - Bahyati, Bahyati; Syafuri, B.; Wasehudin, Wasehudin (Conciencia, 2024)
The aim of this research is to examine how multicultural education is incorporated into PAI learning in vocational schools. This research was conducted at SMKN 4 Cilegon City. The research method uses a qualitative approach. The first data collection method was interviews with school principals, PAI subject teachers and students. The second is documentation and observation. Data analysis techniques include data collection, data reduction, and drawing conclusions. The results of the author's research show that multicultural education in PAI learning: 1) Applying knowledge that upholds the principles of love, openness and respect for each other 2) Recognizing religious tolerance among all members of society in the context of multicultural education in school life.